EFFICACY OF MYOCARDIAL REVASCULARIZATION IN POTENTIAL RECIPIENTS OF HEART WITH THE CHRONIC ISCHEMIC HEART FAILURE - S. V. Gautier; A. B. Mironkov; S. A. Sakhovsky; N. N. Koloskova; I. I. Muminov; E. A. Spirina; I. Yu. Tunyaeva; B. L. Mironkov (Вестник трансплантологии и искусственных органов, 2018)
Aim: to evaluate clinical effi ciency of percutaneous coronary interventions (PCI) at potential recipients of heart with the chronic ischemic heart failure (CHF).Materials and methods. In this retrospective study results of treatment at 76 patients with CHF NYHA III and 36 patients with CHF NYHA IV by scheduled PCI are presented. Duration of observation was from 6 to 160 months. The age of patients at the time of intervention was 61,7 ± 0,62 years (from 33 to 76). 108 male and 4 female. Defi ned life expectancy and echocardiography parameters of the left ventricle (LV) of heart.  Results. 20 patients were died, 16 of them from cardiovascular events. 18 patients during this period undergo orthotopic heart transplantation (HT). The endovascular revascularization leads to LV volumes reduction, increase of ejection fraction and decrease of pulmonary artery pressure. Progress CHF is followed by negative dynamics of these characteristics and need of HT performance. In 74% of cases the effect of myocardial revascularization allows to provide increase in life expectancy of potential recipients of heart with the chronic ischemic heart failure.  Conclusion. Performance of PCI at patients with the chronic ischemic heart failure can delay heart transplantation or become its alternative.